Fiscal federalism, regional public investment and spatial interaction processes: the case of Italy - Giuseppe Di Giacomo; Fabio Mazzola (European Regional Science Association (ERSA), 2010)
The aim of this paper is to examine interregional interactions in public expenditure (for NUTS I and NUTS II level regions) using a new database on Italian Regional Public Accounts (RPA) over the period 1996-2007. Intergovernmental interactions are particularly important for assessing the impact of the reform towards fiscal federalism which is currently under way in Italy. As pointed out by Salmon (1987,2002), a more decentralized system implies that governments situated at the same level in a multi-level governmental system compete each other as well as with those located along the hierarchy. Competitive behavior is also a key element in many recent models of local government behavior (Brueckner, 1997, 2000) and is now the focus of a growing empirical literature based on strategic interaction in local policy decisions analyzed through the estimation of a reaction function (Millimet, 2002; Revelli, 2003). The paper provides empirical evidence on complementary/competitive relationships in terms of capital public expenditure using the approach originally developed by Dendrinos and Sonis (1988, 1990). This model has been applied to income variables in several papers (Hewings et al. 1996, Magalhaes et al.1999, Dall'erba et al., 2003) but the use of policy variables has not been explored yet. By investigating the occurrence of competitive versus complementary interactions in regional public expenditure, the paper suggests that the definition of a fiscal federalism scheme should take into account adequately both direct and indirect effects.
Keywords: 330